Six-Month Effectiveness of Advanced vs. Standard Hybrid Closed-Loop System in Children and Adolescents With Type 1 Diabetes Mellitus - Tornese, Gianluca; Buzzurro, Francesca; Carletti, Claudia; Faleschini, Elena; Barbi, Egidio (Frontiers in Endocrinology, 2021)
Introduction: The purpose of this study was to assess the effectiveness of advanced- (a-HCL) vs. standard-hybrid closed-loop (s-HCL) systems use up to 6 months of treatment in a real-world setting of children and adolescents with T1DM. Methods: We retrospectively evaluated all T1DM pediatric users of MiniMed™ 670G system (s-HCL) and 780G system (a-HCL). HbA1c and BMI were collected at baseline and three and six months after HCL start. Data on glycemic control were extracted from reports generated with CareLink™ Personal Software in Manual Mode, at HCL start, after one, three, and six months after HCL beginning. Results: The study included 44 individuals with a median age of 13.3 years (range 2- 21 years), 20 on s-HCL, and 24 on a-HCL. a-HCL users had a significantly lower HbA1c compared to s-HCL after six months of HCL use (7.1 vs. 7.7%). Significant differences in HbA1c between a-HCL and s-HCL users were found in children aged 7-14 years (7.1 vs. 7.7% after six months) and in those with a worse (HbA1c >8%) glycemic control at the beginning (7.1 vs. 8.1% after six months). No significant changes in HbA1c were found in a-HCL users that previously used s-HCL. Nevertheless, only the use of a-HCL significantly predicted a lower HbA1c after six months. All sensor-specific measures of glycemic control improved from Manual to Auto mode, in both s-HCL and a-HCL, without increasing time spent in hypoglycemia. The percentage of individuals with TIR>70% increased significantly in a-HCL users, who attained this target earlier and more stably: younger age, a higher rate of auto-correction, and a lower amount of CHO inserted predicted a TIR>70%. BMI SDS did not significantly change throughout the study period. Conclusion: This real-world study suggests that effectiveness might be greater in a-HCL than in s-HCL, with significant changes in HbA1c, and reaching earlier and more stably the target of TIR >70%, without increasing hypoglycemia or BMI. Children under the age of 14 years of age seem to benefit the most from a-HCL pumps as well as individuals with the worst glycemic control.